KARAKTERISASI BIOIDIESEL LEMAK IKAN BAUNG (MYTUS NEMURUS) DENGAN KATALIS CaO DARI CANGKANG TELUR AYAM - Pali, Mendriyani; -, Alimuddin; -, Daniel (Jurusan Kimia FMIPA UNMUL, 2016)
The research abaout the use ash of eggchell as source of base catalyst in application for reaction of transseterification from fish baung fat. Conten of base compound in eggchell ash was analyzed by AAS and acidy alkalimetry. The result of the research showed that calcium concentration as carbonat calcium salt in the as of eggchell was 74,8% (w/w). weight variation on the eggchell as catalyst transeterification process is performed to find the optimum reqaction condition if the biodiesel production. Aqquisition of the highest biodiesel yield at catalyst weight of 2,5 % was 96.7663 %. The composition of fatty acid of fish baung fat from transesterification result it is determinate with FT-IR and GC-MS. GC-MS analysis showed that fatty acids are the dominant constituent in the biodiesel is methyl oleate in the amount of 39,39%.